Outcomes of Glucocorticoid Treatment in HBVAssociated Acute-on-Chronic Liver Failure Patients: A Retrospective Observational Study - Xu, Yun; Jiang, Yongfang; Li, Yi (Turkish Journal of Gastroenterology, 2021)
Background: Our study aimed to investigate the effects of glucocorticoid (GC) treatment on liver function, hospitalization length, andexpenses, as well as 28-day mortality in patients suffered from hepatitis B virus (HBV)-associated acute-on-chronic liver failure (ACLF).Methods: This is a retrospective study of 349 patients who were hospitalized with HBV-associated ACLF. Biochemical assay results ofalanine aminotransferase (ALT) level, aspartate aminotransferase (AST) level, total bilirubin (TBil) level, and creatinine (Cr) level both atadmission and before discharge were recorded. GC and antivirus treatment condition, hospitalization length and expenses, as well as28-day status were also recorded.Results: Among 349 patients with HBV-associated ACLF, GC treatment did not benefit in liver function outcomes, and even endedin higher ALT and TBil levels comparing to patients treated without GC. However, patients treated with GC might have lower 28-daymortality. Similar results were shown in patients with or without antivirus treatment. In addition, GC treatment could not shorten hospitalizationlength and could increase the expenses.Conclusion: Using GC in HBV-associated ACLF patients could not improve their liver function, but might reduce the risk of death, nomatter the patient had had antivirus treatment or not. In addition, GC treatment could not shorten hospitalization length and couldincrease the expenses in HBV-associated ACLF patients.